Towards the analysis of the researcher's subjectivity A dialogue between researchers (Clinical Sociology Review, 2023)
This text proposes to reflect on the relationships between researcher and participants in the development of fieldwork and in the information analysis, with emphasis on what happens to the researcher. The proposed reflections are part of our analyzes from research experiences in the socio-educational field and intergenerational, intercultural and interracial relationships. With them we interpellate our social, cultural, age, gender, ethnic/racial places and our privileges. We believe that questioning our involvement, our subjectivity and putting it into dialogue, has contributed to controvert some of the bases of common sense, to unravel the cultural, symbolic and subjective factors that could be reinforcing the structural historical maintenance of the inequalities we face on the topics we cover. Taking into consideration the methodological aspects, this has been possible due to our work from the qualitative methodology approach and, particularly, from the epistemological and methodological approach of clinical sociology, in which we previously found a large part of the discussions that later provoked reflection for the qualitative methodology, which has a strong tradition of reflection on objectivity and epistemological vigilance, to a lesser extent but not in depth on subjectivity and perhaps very little on involvement in research. In this paper we intend to contribute to thinking about these aspects, mainly the implication, from our own subjectivizing processes, because these are always present whether we contemplate them or not.